Disparitas Pendapatan Asli Desa (PADes) dan Pengelolaan Keuangan Dana Desa - Karyada, I Putu Fery; Ayu, Putu Cita; Mahayasa, I Gede Aryana (Jurnal Pendidikan Ekonomi Undiksha, 2020)
Dana Desa have been widely used to increase the village income. However, at present, there is a fairly high PADes gap between villages. This study aim to analyze PADes and financial management of Dana Desa. The research method uses descriptive. Data was collected using surveys and direct interviews with the Perbekel (headman). The results of the study stated that the PADes consisted mostly of village business in the tourism sector. Whereas for the small PADes, they could not take advantage of the village potential so that the source of PADes was from bank interest. In addition, the difference in PADes is due to utilization of Dana Desa on indicators of local potential utilization and community empowerment. Village PADes is high because Dana Desa have focused on programs of utilizing local potential and community empowerment.